Drawing down the moon : witches, Druids, goddess-worshippers, and other pagans in America - Adler, Margot (New York : Penguin Books, 2006)
"Almost thirty years since its original publication, Drawing Down the Moon continues to be the only detailed history of the burgeoning but still widely misunderstood Neo-Pagan subculture. Margot Adler attended ritual gatherings and interviewed a diverse, colorful gallery of people across the United States, people who find inspiration in ancient deities, nature, myth, even science fiction. Contrary to stereotype, what Adler discovered was neither cults nor odd sects, but religious groups that are nonauthoritarian in spirit and share the belief that there is no one single path to divinity." "This fully revised edition of Drawing Down the Moon has been expanded to include an updated resource guide of newsletters, journals, books, groups, and festivals."--BOOK JACKET.
I. Background -- Paganism and prejudice -- A religion without converts -- The Pagan world view -- II. Witches -- The Wiccan revival -- The Craft today -- Interview with a modern witch -- Magic and ritual -- Women, feminism, and the Craft -- III. Other neo-Pagans -- Religions from the past--the Pagan reconstructionists -- A religion from the future--the church of all worlds -- Religions of paradox and play -- Radical Faeries and the growth of men's spirituality -- IV. The material plane -- Living on the Earth -- Epilogue -- Appendix I: Scholars, writers, journalists, and the occult -- Appendix II: Rituals -- Appendix III: Resources.
Previous ed. published by Arkana in 1997.
"The classic study revised and updated with a new resource guide: over 300 listings of groups, festivals, publications, and websites."
Includes bibliographical references (p. [623]-630) and index.
Keywords: Witchcraft -- United States; Cults -- United States; Goddess religion -- United States; Women and religion